Anti-browning and antioxidant properties of Clinacanthus nutans (Burm. F.) Lindau on "Granny Smith" apple juice - Husain, N. F.; Rahman, R. A.; Suleiman, Norhidayah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The effect of anti-browning in Clinacanthus nutans (Burm. F.) Lindau in “Granny Smith” apple juice at two different concentration (0.76 % w/w and 1.52 % w/w) has been investigated. The motivation for this work is to aid the understanding of antioxidant properties in C. nutans, which is important for the anti-browning of apple juice. The measurements have been performed using two methods; total phenolic compound (TPC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay which initially extracts the C. nutans using 50% aqueous acetone at 38 ˚C. It demonstrates these two methods are a suitable and reliable technique to determine the antioxidant activity in both pure apple juice and apple juice + C. nutans mixtures. The finding shows increases of antioxidant properties with a high concentration of C. nutans + apple juice mixture, thus, the presence of C. nutans reduces the browning process of apple juice. This work also provides preliminary indications that the extraction of C. nutans using aqueous acetone has a higher yield of antioxidant compared to the other solvent (water) extraction based on DPPH result. This could have implications for understanding the contribution of antioxidant properties contains in C. nutans towards anti-browning of apple juice and represent important information for the development of healthy drinks.